WTO membership, the membership duration and the utilization of non-reciprocal trade preferences offered by the QUAD Countries - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2021)
This article explores the effect of WTO membership and the duration of this membership on the utilization of non-reciprocal trade preferences (NRTPs) offered by the QUAD countries (Canada, European Union, Japan and the United States). It uses an unbalanced dataset of 136 beneficiaries of NRTPs over the period of 2002-2019. Results based on the two-step system generalized method of moments approach have revealed that over the full sample, both the WTO membership and its duration exerts a strong positive effect on the utilization rate of GSP programs and other trade preferences. WTO members have made a better utilization of GSP programs than of other trade preferences. Meanwhile, as the duration of their WTO membership increases, beneficiaries make more use of other trade preferences than of GSP programs. Additionally, WTO membership and its duration exert different effects on the usage of NRTPs across sub-samples, including in least developed countries versus non-least developed countries on the one hand, and in WTO Article XII members versus non-Article XII members, on the other hand. Finally, there exists a non-linear positive effect of the duration of WTO membership on the utilization of both GSP programs and other trade preferences, whereby the positive effect takes place immediately after entry of a country into the WTO, and its magnitude amplifies for every additional year of WTO membership.
Keywords: F1; O19; 330; WTO membership; Duration of WTO membership; Utilization of unilateral trade preferences utilization; QUAD countries; Developing Countries